(untitled) (Nigerian Journal of Technology, 2016)
This research was conducted to study temperature fluctuation inside the inert atmosphere silos loaded with wheat, compare the temperature fluctuation across the top, middle and bottom part of the silo in relation to the ambient temperature. Temperature readings of the ambient and at the top, middle and bottom part of the two silos for twenty-eight (28) months of storage were recorded in order to monitor temperature fluctuation at different sections inside the inert atmosphere silos loaded with two varieties of wheat namely LACRIWHT-2 (Cettia) and LACRIWHT-4 (Atilla-Gan-Atilla) from Lake Chad Research Institute, Maiduguri, Nigeria. Statistical Analysis System (SAS) software was used to run analysis of variance and t-Test on the data. The findings revealed that there is significant difference in the mean temperature at different position or sections of the silos and as well between the two silos. The mean temperatures at the top, middle and the bottom of the inert atmosphere silos were approximately 29.35 oC, 28.19 oC and 26.51 oC respectively. Temperatures decreases from the top of grain bulk towards the floor of the inert atmosphere silos. http://dx.doi.org/10.4314/njt.v35i3.24